A new xanthyletin-type coumarin from the roots of Peucedanum praeruptorum. Issue 3 (3rd March 2020) - Li, Xin-Yu; Zu, Yuan-Yuan; Ning, Wei; Tang, Ming-Xu; Gong, Chi; Niu, Sheng-Li; Hua, Hui-Ming
Abstract: A new xanthyletin-type coumarin, neopeucedalactone (1 ), was isolated from the roots of Peucedanum praeruptorum Dunn. Its chemical structure was elucidated based on extensive spectroscopic interpretation. The absolute configurations of xanthyletin-type coumarin were determined by comparing experimental and calculated ECD spectra for the first time. Compound 1 exhibited moderate cell growth inhibitory activities in vitro against human leukemic HL-60, THP-1 cell lines, and human prostate cancer PC-3 cell lines, with IC50 values of 9.97, 27.80, and 48.68 µM, respectively.